2006
DOI: 10.1084/jem.20060376
|View full text |Cite
|
Sign up to set email alerts
|

An inflammatory checkpoint regulates recruitment of graft-versus-host reactive T cells to peripheral tissues

Abstract: Transfer of T cells to freshly irradiated allogeneic recipients leads to their rapid recruitment to nonlymphoid tissues, where they induce graft-versus-host disease (GVHD). In contrast, when donor T cells are transferred to established mixed chimeras (MCs), GVHD is not induced despite a robust graft-versus-host (GVH) reaction that eliminates normal and malignant host hematopoietic cells. We demonstrate here that donor GVH-reactive T cells transferred to MCs or freshly irradiated mice undergo similar expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(181 citation statements)
references
References 58 publications
8
173
0
Order By: Relevance
“…Finally, the observed capacity of adapted T cells to condition innate immune response to LPS suggest that stimulation of TLR signaling by opportunistic infection could trigger deleterious inflammatory reaction in bone marrow-transplanted patients (27). This hypothesis is also supported by the observation that bone marrow-transplanted mice with stable mixed blood chimerism exhibit a high sensitivity to LPS challenge (28,29). It remains to be determined whether this situation results from the activity of T cells adapted to recipient's mHA.…”
Section: Figurementioning
confidence: 50%
“…Finally, the observed capacity of adapted T cells to condition innate immune response to LPS suggest that stimulation of TLR signaling by opportunistic infection could trigger deleterious inflammatory reaction in bone marrow-transplanted patients (27). This hypothesis is also supported by the observation that bone marrow-transplanted mice with stable mixed blood chimerism exhibit a high sensitivity to LPS challenge (28,29). It remains to be determined whether this situation results from the activity of T cells adapted to recipient's mHA.…”
Section: Figurementioning
confidence: 50%
“…One final factor likely contributing to the development of lethal X-GVHD in irradiated NOD/SCID-β2m null mice is the probable increased trafficking of xenoreactive huT cells to GVHD target tissues following total body irradiation. Indeed, Chakraverty et al [59] recently showed in a murine allogeneic transplant model that irradiation-induced tissue inflammation is a prerequisite for the migration of alloreactive T cells to GVHD target tissues and the induction of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T cells are important contributors to pulmonary toxicity and T-cell depletion can reduce this toxicity, which is especially relevant for Hurler patients. [25][26][27] Some centers might be reluctant to give pre-emptive DLI because of its potential to trigger GVHD. The reported series represents an investigational approach.…”
Section: Discussionmentioning
confidence: 99%